Colombia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper assesses the monetary policy stance and broad financial conditions in Colombia. It uses a dynamic stochastic general equilibrium model of a small open economy to estimate the neutral rate. A financial conditions index is also constructed to assess overall financial conditions through three different transmission channels (credit, leverage, risk) of the financial sector to the state of the economy. Results reveal that both monetary policy and broad financial conditions in Colombia remained tight in 2016. The results also show that tighter financial conditions could have had a sizable impact on GDP growth.